Actual Purchase on Live Streaming TikTok Shop: The Influence of Trust, Flow Experience, and IT Affordance - Satria Adi Nugraha; Bambang Widjanarko Otok (Eduvest - Journal of Universal Studies, 2025)
The use of live streaming technology has transcended its marketing function, evolving into a platform for fostering deeper interactions between sellers and consumers. The accessibility of technology, trust, and the flow experience play crucial roles in facilitating transactions within the context of live streaming commerce. These factors influence consumer desire to make purchases and ultimately drive actual purchases. This research aims to investigate the influence of these factors on purchase intention and actual purchases within the context of live streaming commerce services in Indonesia. The data analysis method employed is SEM-PLS, with TikTok as the research subject. TikTok, through its TikTok Shop platform, has become one of the primary choices for live streaming commerce services in Indonesia, with 6 million users as sellers and 7 million users as affiliates. The results of this study show that visibility affordance, metavoicing affordance, and guidance shopping affordance can affect purchase intention which in turn affects actual purchases by customers through trust in seller, trust in platform, and immersion. This research not only provides valuable insights for practitioners and sellers in the field of live streaming commerce, but also provides a foundation for the development of technology platforms that meet market needs.